Penentuan Acid Value pada Fatty Acid dengan Metode Titrasi Alkalimetri dan Kromatografi Gas - Syafrinal Syafrinal; Renastio Renastio (Politeknik ATI Padang, 2021)
PT X processes crude palm kernel oil (CPKO) into products such as glycerin, fatty acid, and fatty alcohol. The purpose of this study was to determine the acid value of fatty acid using alkalimetry titration methods and gas chromatography and compare the values obtained with the PT X standard. The results showed that the AV 105 E21 and 105 E22 were following the PT X standard, with ranges respectively 355-365 mg KOH/gr and 268-275 mg KOH /gr. This indicates that the fatty acid samples produced can be sold to consumers.